Reconstruction of the pleistocene paleoclimate from deep groundwater in southern Germany from noble gas temperatures linked with organic radiocarbon dating - Winter, Theis; Aeschbach, Werner; Einsiedl, Florian (Water resources research, 2024)
This study presents a 25 ka reconstruction of the Pleistocene paleoclimate in the South German Molasse Basin. Deep groundwater was sampled at 19 wells in the Upper Jurassic aquifer (UJA). Calculating gas temperatures (NGT) using the UA model with the noble gases Ar, Kr, and Xe led to groundwater recharge temperatures between 0.4 and 4.7°C. Combined with innovative 14CDOC groundwater dating, calculated NGTs revealed up to 8°C cooler soil temperatures during the Pleistocene compared with modern soil temperature. This interpretation agrees well with the observed depleted stable water isotope signature ranging from −83.3 to −86.1 for δ2H and from −10.66 to −11.77 for δ18O, which is characteristic of groundwater of Pleistocene origin in Southern Germany. The temperature differences (∆T) agree remarkably well with calculated NGTs within other European basins (∆T 6-9.5°C) and suggest widespread pronounced terrestrial cooling during the Last Glacial Maximum through the interior of the European continent.